2023
DOI: 10.1186/s43088-023-00350-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural control of V2O5 nanoparticles via a thermal decomposition method for prospective photocatalytic applications

Abstract: Background Recently, transition-metal oxides have represented an exciting research topic, especially their fundamental and technological aspects. Here, vanadium pentoxide nanoparticles (V2O5-NPs) were synthesized through the thermal decomposition of ammonium meta-vanadate. In the current study, we investigated the photocatalytic activity of V2O5-NPs to develop and regulate the V2O5 structure for adsorption applications. Results The obtained nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The photogenerated electrons react with oxygen and generate superoxide anions, which can oxidize the dye molecules (Eq.7.8) . Alternatively, the holes on the surface of V2O5 create hydroxyl radical, which could also mineralize the dye molecules (Eq.9.10) [22,30,37]. This result suggests that the nanocomposite improved degradation efficiency significantly agrees with previous studies [38,39].…”
Section: Mechanism Of the Reactionsupporting
confidence: 82%
See 1 more Smart Citation
“…The photogenerated electrons react with oxygen and generate superoxide anions, which can oxidize the dye molecules (Eq.7.8) . Alternatively, the holes on the surface of V2O5 create hydroxyl radical, which could also mineralize the dye molecules (Eq.9.10) [22,30,37]. This result suggests that the nanocomposite improved degradation efficiency significantly agrees with previous studies [38,39].…”
Section: Mechanism Of the Reactionsupporting
confidence: 82%
“…To unveil the reaction mechanism between adsorbate and adsorbent, the temporary action of the dye adsorption process was studied by the pseudo-first-order and pseudo-second-order models, as described below [22]. The pseudo-first-order rate expression is obtained by [23]:…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…The life cycle analysis revealed that PV systems cannot be considered zero-emission technology due to the potential environmental effects imposed by land use, air quality, water use, the inclusion of hazardous materials, and possible noise/visual pollution; however, these effects can be mitigated by novel technologies such as hybrid power systems and/or floating PV systems [98][99][100]. Overall, future materials for solar photovoltaic devices must balance efficiency, cost, durability, toxicity, availability, and integration to provide a sustainable and cost-effective source of renewable energy [100][101][102][103][104][105][106][107][108].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, nanobiotechnology has become a fundamental branch of current science and a new era in the field of materials science, attracting worldwide interest due to its numerous applications [ 1 ]. The conventional techniques for producing nanoparticles include thermal decomposition [ 2 ], microwave synthesis [ 3 ], electrochemical synthesis [ 4 ], ultraviolet irradiation [ 5 ], laser ablation [ 6 ], laser irradiation [ 7 ], and chemical reduction method [ 8 ]. The fabrication of progressive and clean nanomaterials using several conventional probs, on the other hand, has numerous limitations, such as the use of harmful organic reagents and solvents, the need to elevate the pressure and temperature, and the release of toxic and detrimental byproducts, all of which cause environmental issues [ [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%